Conducting polymer coated graphene oxide reinforced C–epoxy composites for enhanced electrical conduction. (January 2016) - Krushnamurty, K.; Rini, M.; Srikanth, I.; Ghosal, P.; Das, A.P.; Deepa, M.; Subrahmanyam, Ch.
Abstract: Enhanced electrical conductivities were achieved in C–epoxy composites by integrating them with conducting polymers (CPs), namely poly pyrrole (PPY), poly(3, 4-ethylene dioxythiophene) (PEDOT) and graphene oxide (GO) enwrapped by CPs. By in-situ polymerization of pyrrole or 3, 4-ethylenedioxythiophene (EDOT) in the presence of the GO (template), sodium bis(2-ethylhexyl) sulfosuccinate (structure directing agent), ferric chloride (oxidant), the electrically conductive sheets of GO enwrapped CPs were obtained. The formation of CP coating on GO was confirmed by Raman spectroscopy, scanning electron microscopy and thermo gravimetric analysis studies. Different wt% of CP and CP coated GO were added to the epoxy resin and this resin was used to prepare the 2D laminated C–epoxy composites by hand layup method. DC electrical conductivity of the prepared C–epoxy composites were analyzed using current–voltage ( I – V ) characteristics and impedance measurements. Typical results showed that CP coated GO, at 0.5 wt% addition to epoxy imparted highest DC electrical conductivity for C–epoxy composite.